Engaging Gen Y through social network sites / Vincent Wee Eng Kim and Vivien Wee Mui Eik @Bee Jade - Wee, Vincent Eng Kim; Wee, Vivien Mui Eik @Bee Jade (Pusat Penerbitan Universiti (UPENA), 2013)
Social networking sites are able to build on the interactive power of the Internet. This study attempts to discover the influence of social media on the present generation Y as consumers, their buying behaviour and to determine the roles that the social media plays as a popular medium to communicate a message.